Influence of Bilinguism on Socio-Cognitive Personal Development (Zien Journal of Social Sciences and Humanities, 2023)
The article provides an overview of recent foreign studies on the impact of bilingualism on the socio-cognitive development of the individual. Recent experimental scientific research has not only destroyed the myth about the dangers of bilingual development of children, but also showed that it gives much more than just knowing two languages.